A new species of Cyrtodactylus (Squamata: Gekkonidae) from southern Vietnam - Ostrowski, Sabrina; Do, Dang Trong; Le, Minh Duc; Ngo, Hanh Thi; Pham, Cuong The; Nguyen, Truong Quang; Nguyen, van Thi Hong; Ziegler, Thomas (Zootaxa, 2020)
We describe a new species of Cyrtodactylus on the basis of four specimens collected from Phu My, Binh Dinh Province, southern Vietnam. Cyrtodactylus phumyensis sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by a combination of the following characters: size small (SVL up to 66.8 mm); two internasals; dorsal tubercle rows 18 or 19 at midbody; ventral scale rows 33–41; ventrolateral folds slightly developed; each thigh with 5–7 enlarged femoral scales; femoral pores absent in males and female; a series of 5–7 precloacal pores plus a pitted, enlarged precloacal scale in males; 6 pitted, enlarged precloacal scales in female; paravertebral tubercles 20–23; lamellae under toe IV 18–21; small subcaudal scales, not transversely enlarged; two irregular dark longitudinal stripes on shoulder. In phylogenetic analyses, the new species is recovered as a member of the Cyrtodactylus irregularis species group, and strongly supported as a sister taxon of C. cucdongensis from Khanh Hoa Province.